Variety-driven rhizosphere microbiome bestows differential salt tolerance to alfalfa for coping with salinity stress - Fan, Wenqiang; Xiao, Yanzi; Dong, Jiaqi; Xing, Jing; Tang, Fang; Shi, Fengling (Frontiers in Plant Science, 2023)
Soil salinization is a global environmental issue and a significant abiotic stress that threatens crop production. Root-associated rhizosphere microbiota play a pivotal role in enhancing plant tolerance to abiotic stresses. Plants with different genetic backgrounds assemble specific rhizosphere microbial communities to improve their stress resilience. However, limited information is available concerning the specific variations in rhizosphere microbiota driven by different plant genotypes (varieties) in response to varying levels of salinity stress. In this study, we compared the growth performance and rhizosphere microbial communities of three alfalfa varieties with varying salt tolerance levels in soils with different degrees of salinization. Undoubtedly, the increasing salinity significantly inhibited alfalfa growth and reduced rhizosphere microbial diversity. However, intriguingly, different salttolerant varieties exhibited remarkable variations in growth performance and responses of rhizosphere microbiota to salinity. Salt-tolerant varieties exhibited relatively lower susceptibility to salinity, maintaining more stable rhizosphere bacterial community structure, whereas the reverse was observed for salt-sensitive varieties. Bacillus emerged as the dominant species in alfalfa's adaptation to salinity stress, constituting 21.20% of the shared bacterial genera among the three varieties. Salttolerant alfalfa varieties had higher abundances of Bacillus, Ensifer, and Pseudomonas in their rhizospheres. These factors were key determinants of their enhanced salt tolerance. As salinity levels increased, salt-sensitive varieties gradually accumulated a substantial population of pathogenic fungi, such as Fusarium and Rhizoctonia. The differences in rhizosphere microbiota among different varieties ultimately manifested in their functional contributions. Furthermore, our research revealed that the rhizosphere bacteria of salt-tolerant varieties exhibited increased activity in various metabolic pathways, including biosynthesis of secondary metabolites, carbon metabolism, and biosynthesis of amino acids. It is suggested that salt-tolerant alfalfa varieties can provide more carbon sources to the rhizosphere, enriching more effective plant growth-promoting bacteria (PGPB) such as Pseudomonas to mitigate salinity stress. In conclusion, our results highlight the variety-mediated enrichment of rhizosphere microbiota in response to salinity stress, confirming that the high-abundance enrichment of specific dominant rhizosphere microbes and their vital roles play a significant role in conferring high salt adaptability to these varieties.